2022
DOI: 10.3389/fpls.2022.975558
|View full text |Cite
|
Sign up to set email alerts
|

Arbuscular mycorrhizal fungi enhance disease resistance of Salvia miltiorrhiza to Fusarium wilt

Abstract: Salvia miltiorrhiza Bunge (Danshen in Chinese) is vulnerable to Fusarium wilt, which severely affects the quality of the crude drug. Mycorrhizal colonization enhances resistance to fungal pathogens in many plant species. In this study, pre-inoculation of S. miltiorrhiza with the arbuscular mycorrhizal fungi (AMF) Glomus versiforme significantly alleviated Fusarium wilt caused by Fusarium oxysporum. Mycorrhizal colonization protected S. miltiorrhiza from pathogen infection, thereby preventing a loss of biomass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 67 publications
0
8
0
Order By: Relevance
“…In a recent study, it was found that Salvia miltiorrhiza plants when pre-inoculated with AM fungus G. versiforme, a significant reduction in the wilt incidence was observed. Further investigation also revealed that the inoculation of mycorrhizal fungus also upregulated the JA and SA signaling pathways, thereby enhancing the host tolerance to Fusarium wilt (Pu et al 2022). Further studies involving the modulation in phytohormone levels due to AMF association and tolerance to fungal foliar disease need attention from the scientific community.…”
Section: Amf-induced Hormonal Signalingmentioning
confidence: 99%
“…In a recent study, it was found that Salvia miltiorrhiza plants when pre-inoculated with AM fungus G. versiforme, a significant reduction in the wilt incidence was observed. Further investigation also revealed that the inoculation of mycorrhizal fungus also upregulated the JA and SA signaling pathways, thereby enhancing the host tolerance to Fusarium wilt (Pu et al 2022). Further studies involving the modulation in phytohormone levels due to AMF association and tolerance to fungal foliar disease need attention from the scientific community.…”
Section: Amf-induced Hormonal Signalingmentioning
confidence: 99%
“…Our experiment confirmed previous reports (Thygesen et al, 2004;Ashrafi et al, 2014) of the substantial beneficial effects of AM fungus to the growth and photosynthesis capacity of the alfalfa host plants as shown by reduced DI and enhanced alfalfa DW, photosynthesis, and branch number (Tables 2, 3). Similarly, AM fungi have been reported to have positive influence on plant tolerance to disease, for example, Diseases caused by Xanthomonas translucens on wheat (Fiorilli et al, 2018), Fusarium oxysporum on Salvia miltiorrhiza (Pu et al, 2022), and F. oxysporum on tomato (Tanwar et al, 2013).The positive effects were mediated via increased biomass and nutrient acquisition by plants, improved photosynthesis, and activation of plant defense mechanisms. Interestingly, as noted in the Results section, AM fungus enhanced root : shoot ratio of alfalfa infected by pathogens and protection of root biomass in pathogen attack is intuitively likely to enhance plant survival (Tables 2, 3).…”
Section: Discussionmentioning
confidence: 99%
“…In addition to abiotic stress, pathogenic bacteria, fungi, insect pests, virus and other biological stresses disturb orchid medicinal plants during their growth and development and affect the normal growth of plants and quality of herbs ( Jain, Sarsaiya, Chen, Wu, Lu, & Shi, 2021 ). Studies have shown that mycorrhizal fungi can improve the disease resistance of host plants by inducing plant def ence systems, including improving phytohormone concentrations, inducing signal substrate production, regulating gene expression and enhancing protein production ( Weng et al, 2022 , Pu et al, 2022 ). Zhou et al showed that endophytic or mycorrhizal fungi can reduce the incidence rate of root rot disease in D. officinale and enhance the host resistance to Sclerotium delphinii ( Zhou et al, 2020 ).…”
Section: How Does Orm Benefit Host Plants?mentioning
confidence: 99%